Stress and Disease Resistance - Reyes-Lopez, F (Elsevier, 2024)
Short-term and chronic stress modulate or suppress the immune responses in fishes that inhabit an environment that facilitates the dispersion and resilience of pathogens. The allostatic load in disease involves a metabolic trade-off that limits immunocompetence and alters the crosstalk between neuroendocrine, hormonal, and immune axes. In teleosts, the stress- and immune-related cellular populations cohabit in the head kidney, a primary lymphoid and hematopoietic organ that, together with the thymus and secondary lymphoid (spleen, mucosa-associated lymphoid tissues, MALTs) and non-lymphoid organs, orchestrate a typical vertebrate innate-adaptive immune activation, albeit with less specificity in the antigen recognition, less immunological memory, and a higher dependence on cold temperatures than the defensive responses of mammals. B and T cell-mediated adaptive immunity and cytokine-mediated innate immunity depend upon the concerted activation of the hypothalamic-pituitary-interrenal (HPI) and brain-sympathetic-chromaffin (BSC) axes that, through the secretion of cortisol and catecholamines, regulate the immune outcome through their specific receptors on immune cells. Other hormonal axes and exogenous manufactured formulations modulate or stimulate the immune response in fish, preventing or ameliorating the effects of seasonal or local diseases. Overall, the diversity of life cycles and the phenotypic plasticity of fishes have permitted the colonization of new habitats and adaptive radiation that facilitates the survival of populations in stressful habitats by means of changes in the architecture and dynamics of immune components. © 2024 Elsevier Inc. All rights reserved.